Isolation of Some Microbial Agents that cause Acute Gastroenteritis in Children - Ibrahim, Basim M. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Childhood diarrhea remains one of the leading causes of preventable mortality and disease burden throughout the developing world. It generated by several pathologic states, most commonly infections. Although the human large intestine ordinarily harbors a huge microbial population, most bacteria, protozoan, and viral agents of diarrhea are not members of this normal gut flora, but are aquired through contaminated food or water. Objective: This study was conducted to investigate the main microbial causative agent of diarrhea in children below five years of age, and to evaluate the relationship between the incidence of diarrhea with sex and age group of the patients. Patients and Methods: Total of two hundred twenty three stool samples were collected from children under five years of age suffering from diarrhea, who visit Children Welfare Teaching Hospital at Medical City Complex, Baghdad city during the period from July to the end of September 2010. General stool examination (GSE) was done for all the samples to identify the parasitic and fungal agents, and immunological detection were done to identify the viral causative agent of diarrhea, and the pathogenic strains of bacteria. Also biochemical tests for specimen cultured on specific culture media were done to identify the bacterial causative agents, after ensuring that the patients don’t take antibiotics at the time preceding sample collection. Results: Pathogenic bacteria came first with higher number of microbial isolates. High number of bacterial isolates was related to Enteropathogenic Escherichia coli (EPEC). Entamoeba histolytica appears as the most frequent parasitic causative agent. Increased rate of infection were falls on the first and second age groups, and also high rate of infection were recorded in males than in females. Conclusion: bathogenic bacteria appear as the most predominant causative agent of infectious diarrhea in males under two years of age.